PERAN MEDIA SOSIAL INFLUENCERS DAN KEPERCAYAAN MEREK SEBAGAI MEDIATOR TERHADAP NIAT BELI PRODUK SKINCARE DI KOTA AMBON - Victor Ringhard Pattipeilohy; Vascolino Pattipeilohy (Politeknik Negeri Ambon, 2025)
Intriduction: The role of social media influencers in marketing has become increasingly important, as they are capable of boosting company sales. The purpose of this study is to examine and analyze the role of social media influencers on brand trust and purchase intention of skincare products in Ambon City. Methods:This research employs a quantitative approach. The research instrument used is a questionnaire for data collection purposes. The population consists of all skincare product consumers, with the total number unknown, and the sample comprises 100 respondents. A non-probability sampling method was used, specifically the purposive sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) with the SmartPLS 3 application. Results:The results show that all hypotheses are supported. The role of social media influencers has a positive and significant direct effect on brand trust and purchase intention of skincare products, as well as an indirect effect mediated by brand trust. Brand trust is proven to serve as a mediating variable, although only partially. Furthermore, brand trust also directly has a positive and significant influence on the purchase intention of skincare products. Keyword: Media Sosial Influencer, Brand Trust, Purchase Intention